FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL DI PUSKESMAS LUBUK BUAYA PADANG - Eliwarti Eliwarti (STIKes Al-Insyirah Pekanbaru, 2020)
Pregnancy check is very important to detect the risk of abnormalities in pregnancy. From 22 puskesmas in Padang city, Puskesmas Lubuk Buaya the most visited, based on the data that was researcer collect from some source in 2017 have 2.141 ( 95,6%) visiter and 2018 as much 2.102 (97,7%) so the conclusion from that data any decreasing visiter as mach 2,1 %. And also in 6 month before that problem still happen till now in there. This study aims to determine the factors associated with the visit Antenatal care in pregnant.The type of research is descriptive analytic with cross sectional design. Conducted in Lubuk Buaya Health Center with a population of 138 people, the sample was taken by Accidental Sampling as many as 58 people with questionnaires and checklists. Computerized data processing, in univariate analysis with frequency distribution and bivariate using uju chi square.The result of this research is 63,8% visit Antenatal care to pregnant mother is not good, 60,3% pregnant women have low knowledge, 55,2% pregnant women have negative attitude and 58,6% family does not support, there is significant relation between Knowledge (p = 0,001), attitudes of pregnant women (p = 0,005) and family support (p = 0,001) to visit of Antenatal Care in pregnant woman at Puskesmas Lubuk Buaya.